Profiling of illicit erimin 5 tablet seized in Malaysia / Rusyidah binti Abdul Rahim - Abdul Rahim, Rusyidah (2013)
Profiling study of fourty - six illicit Erimin 5 tablet samples were carried out according to their physicals and chemical characteristics. Out of 46 illicit Erimin tablet samples, 45 tablet samples were peach-orange like in colour and only one tablet sample was green coloured tablet. For physical characteristic studies, logo and color were observed whereas, others characteristics such average weight of tablet, thickness and diameter of the illicit Erimin 5 tablet samples were measured and photograph was taken. The distribution profile of average weight of tablet, diameter and thickness of the tablet samples were developed. For chemical characteristics, these illicit Erimin 5 tablet samples were characterized according to their active ingredients, adulterants, diluents and dyes. Active ingredients and adulterants were analyzed by GCMS and diluents were used ATR-FTIR. Dyes of tablets were determined by TLC using two different systems. Nimetazepam content (percentage) and the weight of nimetazepam per tablet were determined using HPLC and their distribution profiles were developed. Nimetazepam, Diazepam and Nitrazepam together with caffeine (adulterant) were detected as active ingredient with Lactose, Mannitol and Calcium phosphate as diluent. Sunset Yellow alone / combination with others dyes namely Ponceau 4R and/or Tartrazine were found in peach-orange like tablet samples and combination of Brilliant blue and Tartrazine were detected in green coloured tablet sample.